Intergroup Economic Inequality in South Africa: The Post-Apartheid Era - Sherer, George (American Economic Review, 2000)
One of the most pressing challenges facing the South African government is how to expand the overall opportunity set for nonwhites who have been historically disadvantaged by apartheid. This is perhaps best accomplished by expanding employment opportunities within the economy. General employment expansion mnust be accomplished keeping in mind the urgent need to radically expand nonwhite employment. Employment and unemployment statistics are difficult to interpret. But there is a general sense that the unemployment situation, especially for nonwhites is, extremely bad. In dealing with employment issues, two concerns must be faced. Both are legacies of the apartheid era. The first is related to differences in educational attainment across racial groups. During apartheid, the Bantu Education policy was designed to suppress the educational attainment of Africans (blacks) relative to whites. However, educational opportunities for coloureds (mixed race) and Asians (primarily Indian) were also depressed relative to whites. The second concern is that labor-market discrimination could be used either to exclude nonwhites for employment consideration or to limit their wages and opportunities once they are employed. For policy reasons it is imperative to understand the extent to which premarket or market factors operate to limit opportunities for nonwhites. Given the institutionalized nature of apartheid segregation, one can imagine three scenarios. Earnings differences could be the result entirely of premarket factors such as education differences. Alternatively, earnings differences could be the result of labor-market practices that limit one group' s eamings relative to another's. A third scenario, a synthesis of the former two, would find earnings differences to be the result of a combination of premarket differentials and in-market discrimination. To address premarket discrimination, policy would focus entirely on leveling funding and increasing access to educational opportunities for historically disadvantaged groups. However, legislative forms such as affirmative action would be required to remedy exclusively labormarket discrimination. A combination of these policies would be required to deal with the third scenario. Understanding the relative importance of these factors is important when resource allocation is considered. This paper concerns itself with measuring income losses to nonwhites from labor-market discrimination. To evaluate the extent of labor-market discrimination, ordinary least-squares (OLS) estimates of earnings equations are evaluated for males in each population group. Observed wage differentials are decomposed into a component attributable to human-capital differences while a residual is attributed to labor-markelt discrimination. These findings are then contrasted to those of others to give a sense of the trend in market discrimination in South Africa.